2013
DOI: 10.1002/grl.50714
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic topologies of an in vivo FTE observed by Double Star/TC‐1 at Earth's magnetopause

Abstract: [1] Flux transfer events (FTEs) are magnetic flux ropes formed at planetary magnetopauses (MPs). Although evidence suggests that FTEs form through time-dependent magnetic reconnection, details of that process and 3D structure of the flux ropes remain largely unclear. This letter presents Double Star/TC-1 data of an FTE occurred on 7 April 2004 which show that the FTE was separated by two X-lines moving south-dawnward. In particular, the electron energy-pitch angle distribution implies that the FTE was composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 32 publications
9
70
2
Order By: Relevance
“…Inside the flux rope, almostisotropic energetic electrons were clearly identified, while the energy flux intensity is weaker than that in the magnetosphere, consisting of the re-closure of the field lines in the flux rope. This is different with large-scale flux rope situations, in which both trapped and untrapped electrons can be observed, suggesting different topologies of magnetic field lines (Pu et al, 2013;Roux et al, 2015). At the sheath side (from 19:58:05.0 to 19:58:06.2 s), energetic electrons only in the antiparallel directions were detected, suggesting the existence of another X line on the north-dusk side to generate these open field lines, and also this X line was formed earlier than the one at the dawn side.…”
Section: Observationcontrasting
confidence: 62%
See 1 more Smart Citation
“…Inside the flux rope, almostisotropic energetic electrons were clearly identified, while the energy flux intensity is weaker than that in the magnetosphere, consisting of the re-closure of the field lines in the flux rope. This is different with large-scale flux rope situations, in which both trapped and untrapped electrons can be observed, suggesting different topologies of magnetic field lines (Pu et al, 2013;Roux et al, 2015). At the sheath side (from 19:58:05.0 to 19:58:06.2 s), energetic electrons only in the antiparallel directions were detected, suggesting the existence of another X line on the north-dusk side to generate these open field lines, and also this X line was formed earlier than the one at the dawn side.…”
Section: Observationcontrasting
confidence: 62%
“…The magnetic flux rope is usually regarded as the physical model of the flux transfer event (FTE) (Russell and Elphic, 1978) on Earth's magnetopause, with spatial sizes extending from several ion inertial lengths (d i ) to a few Earth radii (R E ) (e.g., Hasegawa et al, 2010;Eastwood et al, 2016). Recent in situ observations revealed that flux ropes could be flanked by two converging plasma jets, indicating these flux ropes are still active, and possibly generated by multiple, or even sequential, X-line reconnection (Hasegawa et al, 2010;Øieroset et al, 2011;Pu et al, 2013). Such active flux ropes are relatively less often observed in a statistical study (Zhang et al, 2012); thus, X lines flanking flux ropes might be short-lived once these flux ropes convect away from the generation region.…”
Section: Introductionmentioning
confidence: 99%
“…We interpret this sequence of observations as the signature of the successive crossing of the two flux tubes by the spacecraft. These two flux tubes may have been generated by multiple sequential reconnection process, which is expected to occur under strong B Y and negative B Z IMF conditions, as was observed for a long time around the event (e.g., Pu et al, ; Raeder, ). The first flux tube (FT A ) contained trapped electrons.…”
Section: Discussion and Interpretationmentioning
confidence: 88%
“…Aside from large‐scale FTEs often observed at the magnetopause, small‐scale perturbations with magnetic signatures akin to those of FTEs might indicate the existence of very localized magnetic island structures (Hesse et al, ). Such magnetic islands may also be generated by multiple X‐line reconnection (Pu et al, ; Zhong et al, ) (i.e., between two X‐lines created sequentially on the magnetopause) or at a single X‐line owing to rapid variations of the reconnection rate (Huang et al, ). Their typical signatures are an enhancement of the total magnetic field strength and a magnetic bipolar signature (Teh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in the original Russell and Elphic [] model a poleward acceleration of the plasma could be detected inside the FTE, but the velocity increase should be observed during the entire FTE and not only at its trailing edge [ Sonnerup , ]. In the multiple X line model [ Lee and Fu , ], two converging reconnection jets at the borders of the FTE are expected if the FTEs are observed during their formation [ Hasegawa et al , ; Trenchi et al , ; Øieroset et al , ; Zhang et al , ; Zhong et al , ; Pu et al , ]. The lack of the southward reconnection jets at the leading edge of the FTEs could be explained possibly also in the context of multiple X line reconnection, if reconnection at the southern X line is more active and reconnection at the northern X line is not active when the FTEs are detected.…”
Section: Discussionmentioning
confidence: 99%